Perception of Employers Regarding the Employability Skills Required by Graduates - M Mazlan, Nur Syahirah; Rahim, Mohd Bekri (Research and Innovation in Technical and Vocational Education and Training, 2025)
The rapid development of technology and globalization, particularly with the challenges of the Fourth Industrial Revolution (IR 4.0), has transformed the global labor market. Graduates now not only need to possess high academic qualifications but also employability skills such as communication, problem-solving, and the ability to adapt to technological changes. In Malaysia, graduate employability has become a major issue, with a lack of relevant skills among graduates. This study aims to assess employers’ perceptions of the employability skills required by graduates in the Mechanical and Construction sectors. The research design used is a survey method with a quantitative approach, utilizing questionnaires involving 70 respondents from both sectors around Batu Pahat, Johor. Six main elemenons assessed are leadership skills, communication, teamwork, problem-solving, information and communication technology (ICT), and English proficiency. Data were analyzed using descriptive statistics and independent T-test to determine the differences between the two sectors. The findings of the study show that leadership, teamwork, and problem-solving skills received the highest mean scores in both sectors, with employability levels rated as moderately high. Independent T-test analysis indicates no significant differences in employers’ perceptions between the Mechanical and Construction sectors regarding these elements. Although there are slight variations in mean scores between the sectors, the results reflect that the employability skill requirements are almost similar in both industries. This study suggests that higher education institutions should adapt their curriculum and skills training to ensure that graduates are better prepared with relevant skills. Additional emphasis should be placed on communication, leadership, ICT, and English proficiency, especially in the era of rapid digitalization and globalization. Overall, this study provides guidance to graduates, employers, and educational institutions in enhancing graduate employability and meeting the dynamic needs of the Mechanical and Construction industries.